Stem cell niche: methods and protocols - Turksen, Kursad (Methods in molecular biology, 2013)
Immunostaining of Germline Stem Cells and the Niche in Drosophila Ovaries -- Identification of Male and Female Germline Stem Cells in Drosophila -- Visualization of Adult Stem Cells Within their Niches Using the Drosophila Germline as a Model System -- Morphometric Evaluation of the Spermatogonial Stem Cell Distribution and Niche in Vertebrates -- In vitro Construction of 2D and 3D Simulations of the Murine Hematopoietic Niche -- Isolation of Embryonic Hematopoietic Niche Cells by Flow Cytometry and Laser Capture Micro-Dissection -- Isolation and Enrichment of Stro-1 Immunoselected Mesenchymal Stem Cells from Adult Human Bone Marrow -- Primary Marrow Derived Stromal Cells: Isolation and Manipulation -- Detection In vitro and Quantitative Estimation of Artificial Microterritories Which Promote Osteogenic Differentiation and Maturation of Stromal Stem Cell -- The Prospective Isolation of Viable, High Ploidy Megakaryocytes from Adult Murine Bone Marrow by Fluorescence Activated Cell Sorting -- Looking for the Niche: Substance Delivery into the Lateral Ventricle of the Brain: The Osmotic Minipump System -- Unbiased Stereological Method to Assess Proliferation Throughout the Subependymal Zone -- Cardiac Stem Cell Niche, MMP9, and Culture and Differentiation of Embryonic Stem Cells -- Human and Murine Skeletal Muscle Reserve Cells -- Modulation of the Host Skeletal Muscle Niche for Donor Satellite Cell Grafting -- Isolation of ckit+ Human Amniotic Fluid Stem Cells from Second Trimester -- Hypoxia and Visualization of the Stem Cell Niche -- Detection and Isolation of Human Disseminated Tumor Cells in the Murine Bone Marrow Stem Cell Niche -- Identification and Separation of Normal Hematopoietic Stem Cells and Leukemia Stem Cells from Patients with Acute Myeloid Leukemia -- Serial Orthotopic Transplantation of Epithelial Tumors in Single-Cell Suspension -- Isolation and Propagation of Colon Cancer Stem Cells.